Bahasa Indonesia sebagai Sarana Diplomasi Budaya di Kancah Internasional - Wibi Ramdhan (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
Indonesian language holds a strategic role as a tool of cultural diplomacy on the international stage. As a symbol of national identity, it is utilized to showcase Indonesia's cultural richness through various programs such as Bahasa Indonesia for Foreign Speakers (BIPA) and the use of digital media. This strategy not only strengthens Indonesia’s positive image globally but also promotes harmonious international relations based on soft power. Despite challenges in digitalization and cross-sector coordination, the Indonesian language has great potential to become a leading language in Southeast Asia. Through innovative approaches and cross-sector collaboration, cultural diplomacy based on the Indonesian language is expected to contribute to better global relations.